Cannabis Use Is Associated With Recurrence After Primary Spontaneous Pneumothorax - Wakefield, Connor J.; Seder, Christopher W.; Arndt, Andrew T.; Geissen, Nicole; Liptay, Michael J.; Karush, Justin M. (Frontiers in Surgery, 2021)
Purpose: Primary spontaneous pneumothorax (PSP) is a frequently encountered entity that carries a high rate of recurrence. The current study aims to investigate if cannabis use at time of initial PSP is associated with disease recurrence. Methods: Patients presenting with PSP between 2010-2018 at a single institution were identified. Exclusion criteria included secondary pneumothorax, severe chronic lung disease, lung cancer, and lost to follow-up. Patients were compared relative to their marijuana usage with Fisher’s Exact test, Wilcoxon rank-sum test, and logistic regression. Results: Overall, 67 patients (53 male) met inclusion criteria with a median BMI of 21.5 kg/m2 (IQR 19.1-25.2) and age of 34 years (IQR 22-53). Initial treatment consisted of chest tube in 42 patients (63%), video-assisted thoracoscopic surgery wedge resection in 19 patients (28%), and observation in 6 patients (9%). Cannabis users (n=28; 42%) had a higher rate of tobacco use (79% vs. 38%; p= 0.005), lower BMI (21.0 kg/m2 [IQR 18.3-23.1] vs 22.2 kg/m2 [IQR 19.9-28.6], p=0.037), and were more likely to require intervention at first presentation compared to non-cannabis users. Cannabis use was associated with PSP recurrence when adjusting for tobacco use, lung disease, BMI, and height (OR 1.85, 95% CI 1.38-18.3, p = 0.014). Conclusion: There is a high rate of cannabis usage in patients presenting with PSP. Cannabis usage is associated with PSP recurrence and eventual need for operative intervention.